PENYELESAIAN SENGKETA WANPRESTASI DALAM PERJANJIAN JUAL BELI HASIL PERTAMBANGAN - Vio Astari; Gio Vanny Listanio; Susan Celine Chandra; Muhammad Iqbal Tarigan (JURNAL RECTUM: Tinjauan Yuridis Penanganan Tindak Pidana, 2019)
The form of the mining product sale and purchase agreement that is carried out by both the seller and the buyer is done in written from, namely the agreement made and agreed by both parties. This is intended to avoid things that are not desirable later on, so that the agreement can be used as evidence to clarify the rights and obligations of each party and to end an agreement between the two parties. The purpose of this study was to find out the regulating of the permit for the buying and selling of mining products, to find out the form of default in the sale and purchase agreement of mining products in the decision No.143 / Pdt.G / 2014 / PN. Mdn and to analyze the judge's judgment on the decision No.143 / Pdt.G / 2014 / PN. Mdn in resolving mining product disputes. The type of research used was normative law. The nature of the research was descriptive. Data sources were obtained from primary, secondary and tertiary legal materials. Data analysis applied qualitative approach. The results of the research showed that in the form of default in the mining product sale and purchase agreement in addition to the issue of profit, it is also obligatory to provide a way out and land acquisition of plants to the mining site and bore road operating costs along with the costs of fostering local communities. This was stated in Decision No. 143 / Pdt.G / 2014 / PN.Mdn where after a dispute occurred, the settlement was carried out through Medan District Court because it was not successfully resolved through a non-litigation process.